IMPROVING THE STUDENTS’ WRITING SKILLS OF NARRATIVE TEXT THROUGH BEYOND CENTERS AND CIRCLE TIME METHOD - Wati Hasibuan, Fatma (Faculty of Tarbiyah nad Teacher Training, 2023)
This research was aimed to improve the students’ writing skill of narrative text through beyond centers and circle time method. The subjects of this study were 25 students at 10th grade in vacational high school MAS AL-HIDAYAH. This research was conducted by using classroom action research that consist of 2 cycles. The technique of analyzing data for quantitative data was the students’ score of test. While for qualitative data, the researcher used the technique by Miles and Huberman. The result of this research showed that the mean of the students score was 54,72 in which there were 5 from 25 students who passed the standart minimum score or KKM. In the post test I, there were 10 or 20% who improved and the score mean was 65,12. Meanwhile, in the post test II, the mean score was 78,12. There were 18 students or 72% passed the standart minimum score. It indicated that beyond centers and circle time method could improve the students’ writing skill of narrative text. This result is strengthened by the observation and the interview result that students were more active in the class and enjoy the learning process. They were also active in learning proccess.